(untitled) (Research, Society and Development, 2020)
In Brazil, the syphilis has presented itself as an epidemic due to its high incidence, and it is an infectious disease but that has been neglected in health care. When diagnosed in pregnancy it is called gestational syphilis, and it can progress to premature birth, spontaneous abortion, perinatal death and congenital syphilis. The objective of the article is to describe the epidemiological profile of notified cases of syphilis in pregnant women between 2014 and 2018 in the State of Piauí using data from the National Notifiable Diseases Surveillance System (NNDSS). This is an epidemiological, documentary, retrospective, descriptive study with a quantitative approach. The data collection is equivalent to the cases of syphilis in pregnant women notified in the NNDSS, from 2014 to 2018 in the State of Piauí, these being made available by the SUS Computer Department (DATASUS), tabulated by TABNET and processed in Microsoft Excel. The data was analyzed according to the socio-cultural and clinical variables of the pregnant women: age group, educational level, gestational age, treatment scheme and clinical classification. In the results obtained, 1.954 cases of syphilis were reported in pregnant women. The age group between 20 and 29 years old prevailed (49.3%). The 3 rd gestational trimester presented the highest number of notifications 808 (41.3%). As for the clinical classification, the latent form prevailed with 646 cases (33%). Concludes that in recent years there has been an increase in notifications of syphilis in pregnant women in Piauí, and that the state needs support and planning for the adhesion of strategies to control and eradicate this preventable and treatable condition.